Development of a prototype intelligent diagnostic systems of heart diseases based on the ECG waveform - Sheikh Hussain Shaikh Salleh, 1958-; Malarvili Bala Krishnan; Persidangan Sempena Pameran Penyelidikan dan Pembangunan IPTA (2003 : Kuala Lumpur ) (Skudai : Universiti Teknologi Malaysia, 2003)
42